Effect of leave extract of Ocimum basilicum on deltamethrin induced nephrotoxicity and oxidative stress in albino rats - Saber A. Sakr, Wael M. Al-Amoudi (Journal of Applied Pharmaceutical Science)
Deltamethrin is a pyrethroid insecticide used extensively in pest control. On the other hand it showed different toxicity in mammalian animals. Basil or sweet basil (Ocimum basilicum) is a plant which showed many pharmacological effects. The present work studied the potential protective effect of Ocimum basilicum extract on deltamethrin-induced nephrotoxicity in albino rats. Treating animals with deltamethrin induced several histopathological alterations in the kidney. The renal tubules lost their characteristic appearance and their lining epithelial cells were degenerated. The glomeruli were atrophied and the renal blood vessels were dilated and congested. The intertubular spaces were infiltrated by inflammatory leucocytic cells. Marked elevation in serum creatinine and urea was recorded. Moreover, deltamethrin increased significantly the concentration of malondialdehyde (MDA) and decrease the activities of superoxide dismutase (SOD) and catalase (CAT) in renal tissue. Treating animals with deltamethrin and aqueous extract of basil led to an improvement in histological and biochemical alterations induced by deltamethrin. The biochemical results showed that creatinine and urea appeared within normal level. Reduction in the level of MDA (lipid peroxidation marker) and increase in the activities of SOD and CAT was recorded. It was concluded from this study that basil aqueous extract has a beneficial impact on deltamethrininduced nephrotoxicity in albino rats by its antioxidant effect.
Keywords: Deltamethrin, Nephrotoxicity, Basil, Oxidative stress.